The Effect of Prediction Strategy toward Students’ Reading Comprehension for the Tenth Grade Students at SMAN 8 Muaro Jambi - Rimarta Maharani Prastika; Yanti Ismiyati; khidayatul Munawwaroh (JELT: Journal of English Language Teaching, 2020)
This research was aimed to find out whether there was any significant effect of prediction strategy toward students’ reading comprehension for the tenth grade students at SMAN 8 Muaro Jambi. The research methodology of this study was true-experimental research which involved experimental class and control class. The total population of this research was the tenth grade students of SMAN 8 Muaro Jambi, which consisted of 225 students. The researcher used 2 classes as the sample of this study. These 2 classes were divided into experimental and control class. There were 28 students at experimental class (X Science 1) and 29 students at control class (X Science 2). In collecting the data, the researcher gave pre-test, treatment, and post-test to both classes. The formula used to analyze the data was t-test. The researcher found that the pre-test mean of experimental class was 60,35 and post-test was 83,57. Meanwhile, the pre-test mean of control class was 55,51 and post-test was 68,96. Furthermore, the researcher discovered that tobservation was 11,63, whereas the ttable was 2,004 for a = 0,025. This data showed that tobservation was higher than the ttable (11,63>2,004), so, was accepted and was rejected. As a result, there was any significant effect of prediction strategy toward students’ reading comprehension for the tenth grade students at SMAN 8 Muaro Jambi.Key Words: Prediction Strategy, Reading, Students’ Reading Comprehension.